Characteristics of chondroid lipoma: A case report and literature review - Huang, Chao (Medicine (Baltimore), 2019)
RATIONALE: Chondroid lipoma (CL) is a rare benign tumor. No relevant epidemiological reports have been published on CL, and there is a lack of uniform diagnostic and treatment criteria for the tumor. PATIENT CONCERNS: Here, we report a case of CL with a mass on the left buttock for 2 weeks, and further illuminate its diagnosis and treatment. DIAGNOSIS: The diagnosis of CL was rendered according to the pathological indices. INTERVENTIONS: The tumor was resected completely under spinal anesthesia. OUTCOMES: The patient was followed-up for 6 months and showed no tumor recurrence or metastasis and there was resolution of the patient's lower-limb numbness and pain. LESSONS: The case study presented here provides evidence that CL could be effectively diagnosed by using ultrasound, puncture or biopsy, and/or magnetic resonance imaging. Furthermore, the patient recovered without any complications after completely resecting the tumor.